Carbon monoxide promotes stomatal initiation by regulating the expression of two EPF genes in Arabidopsis cotyledons - Weng, Xianjie; Zhu, Lingyan; Yu, Shuangshuang; Liu, Yue; Ru, Yanyu; Zhang, Zijing; He, Zhaorong; Zhou, Lijuan; Chen, Xiaolan (Frontiers in Plant Science, 2022)
The gaseous molecule carbon monoxide (CO) can freely pass through the cell membrane and participate in signal transduction in the cell to regulate physiological activities in plants. Here, we report that CO has a positive regulatory role in stomatal development. Exogenous CO donor CORM-2 [Tricarbonyldichlororuthenium (II) dimer] treatment resulted in an increase of stomatal index (SI) on the abaxial epidermis of cotyledons in wild-type, which can be reversed by the addition of the CO biosynthesis inhibitor ZnPPIX [Protoporphyrin IX zinc (II)]. Consistent with this result, mutation of the CO biosynthesis gene HY1 resulted in a decrease of SI in hy1-100 plants, while overexpression of HY1 led to an increase of SI. Further investigation revealed that CO acts upstream of SPCH and YDA in the stomatal development pathway, since the loss of function mutants spch-1 and yda-2 were insensitive to CORM-2. The expression of EPF2 was inhibited by CORM-2 treatment in wild type and is lower in hy1 than in wild-type plants. In contrast, the expression of STOMAGEN was promoted by CORM-2 treatment and is higher in HY1-overexpression lines. Loss of function mutants of both epf2 and stomagen are insensitive to CORM-2 treatment. These results indicated that CO positively regulates stomatal initiation and distribution by modulating the expression of EPF2 and STOMAGEN.